Identifikasi dan Pemetaan Risiko Usahatani Jamur Merang (Volvariella volvaceae) - Trimo, Lucyana; Hidayati, Syarif; Pardian, Pandi (Universitas Galuh, 2025)
Karawang Regency is one of the straw mushroom production centers in West Java Province. The harvest area for straw mushroom cultivation in Karawang Regency continues to decline from year to year. There are many risks faced in the straw mushroom cultivation business which affect production dynamics. However, the potential and opportunities for the straw mushroom business development in Karawang are still quite high. Karawang is one of the rice production areas in West Java, so the availability of straw as a growing medium will be quite abundant . The aim of this research is to identify risks that often occur and mapping the risks faced by straw mushroom farmers at Jatisari Subdistrict. This research was conducted using a mixed method research method. The data was analyzed descriptively and also using the House of Risk (HOR) phase-1. The results of this research are: (1) based on the level which appears most frequently, the risks faced by farmers in growing straw mushrooms are: low price of straw mushrooms, lack of capital, and fluctuation of selling price of straw mushrooms. Meanwhile, the level of risk that occurs least frequently are: crop failure, lack of access to financial institutions, and long disbursement of bank loans; (2) based on the results of risk mapping, there are eight priority risk agents that must be mitigated, i.e.: lack of capital, low fluctuating selling price, high expenditure of farmers needs, mushroom sales are not smooth enough, long disbursement of bank loans, high bank interest, and financial institutions (banks) access difficulties.